A state of the art fuzzy based healthcare risk management for health information exchange - Rao Thangeda, Amarendar; Coleman, Alfred (International Journal of Engineering and Technology, 2019)
The Today health-care organizations and physicians use several processes and instruments to exchange data about the private health of patients electronically. The main aims of the different methods of information (HIE) exchange on health are to reduce healthcare costs, to minimize medical errors and to better coordinate health services. Risks of information assets have a complex nature and different approaches address risk management of information security in medial field. The objective of this paper is to create the state-of - the-art information security risk management. In order to accomplish this, a Fuzzy based Healthcare Risk Management is suggested. This research aimed at exploring the core importance of the Fuzzy based Healthcare Risk Management (FHRM) from the views of health care consumers in the health sector. The result shows that the views of patients on multiple mechanisms for exchanging data about patient privacy, trust in competence and integrity and readiness to share data are significantly different.Â Â Â